CONIDIAL FUNGI FROM Salix herbacea LEAF LITTER AND THEIR GROWTH TEMPERATURE PREFERENCES - Oliveira Longa, Claudia Maria; Palma, Luisa; Tosi, Solveig (Boletín Micológico, 2005)
A preliminary qualitative analysis was carried out on fungal composition of leaf litter of Salix herbacea growing on Gran Sasso, Monti della Laga (TE), the highest mountain of the Apennines. Direct isolation in humid chamber and culture of soil on plates were used as methods. The most isolated genera were Acremonium, Cladosporium, Lecanicillium, Mucor, Penicillium and Pestalotia. Lag period and radial growth of the colonies were recorded at different temperatures from -1 to 45ºC. and the optimal temperature for growth and sporulation was detected for each isolate. Most of the isolated strains were psychrotolerant mesophyle and capable to grow within a 1ºC to +30ºC range, except for a thermotolerant strain of Penicillium that could grow at 45ºC .They exhibited a wide range of thermal tolerance together with their ability to grow in habitats which are commonly submitted to great changes in temperature similar to those occurring in alpine climate. Data presented in this paper can be useful to understand the ecological requirements of the fungal components of high mountain ecosystems that are often subject to monitoring in the investigation of the effects of global climatic changes.